ANALISIS PREFERENSI MASYARAKAT TERHADAP PRINSIP BAGI HASIL PADA BANK SYARIAH DI WILAYAH BANDA ACEH - Vebitia, Vebitia; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The objective of this research is to analyze ho peoples preference against sharing principle on Islamic banks in the region of Banda Aceh. the research type used in this research is study of literature (library research) and nature of study in this research is descriptive study. The data types used is primary data. Primary data gotten from interview by asking questions to the customers of Islamic banks in the region of Banda Aceh. the analysis method used in this research is descriptive method. The result of this research showed that the main reason for choosing Islamic banks is the religious reason. Islamic banks is halal, free from riba, as well as more promising for the good of the hereafter. Customers have a strong desire to save on Islamic banks due to avoid riba. Islamic banks profit sharing rate is also influence the decision in choosing the Islamic banks.Keywords: public preferences, profit sharing, Islamic banks